ANALISIS PENGARUH DIFERENSIASI PRODUK, KUALITAS PRODUK, KUALITAS LAYANAN DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PENGAMBILAN KPR (KREDIT PEMILIKAN RUMAH) - Ayodya, Dewanda; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
This study aims to determine the diferentiation product, product quality, service quality and consumer attitudes toward decision-making KPRib Sharia and analyze the most dominant factor in influencing the decision-making KPRib Sharia.This research was conducted at Bank OCBC NISP Syariah Branch Semarang. Methods of data collection in this study is by questionnaires filled out by respondents are customers of Bank OCBC NISP Syariah Branch of Semarang who had conducted an KPRib, samples were taken of 100 respondents. The sampling technique in this research is non probability sampling with purposive sampling method.Results of regression analysis showed that the variables of diferentiation product,, product quality, service quality and consumer attitudes positive influence on the decision-making KPRib Bank OCBC NISP Syariah.